Long‐term efficacy of lymphovenous anastomosis for the treatment of retroperitoneal lymphangiectasia: A case report and a review of literature. Issue 1 (11th January 2022) - Lee, Christina Dami; Kwiecien, Grzegorz; Wenzinger, Eric J.; Lee, Irene; Cakmakoglu, Cagri; Schwarz, Graham S.
Abstract: Lymphovenous anastomosis (LVA) represents an alternative treatment for retroperitoneal lymphangiectasia. In contrast to sclerotherapy or excision, which may risk lymphatic obstruction and subsequent lymphedema, LVA preserves existing lymphatic architecture and transit. This report shows long‐term efficacy of LVA for functional decompression of a symptomatic pathologically dilatated retroperitoneal lymphatics. A 47‐year‐old female with retroperitoneal lymphangiectasia refractory to multiple percutaneous drainages and treatments with sclerosing agents underwent LVA with anastomosis of a dominant segment of retroperitoneal lymphangiectasia to the deep inferior epigastric vein. Postoperative serial magnetic resonance imaging with 3‐dimensional volume calculation over the 27 months follow‐up showed evidence of decompression of the lesion with patent bypass. There were no known immediate complications nor requirement of further interventions. The patient's subjective pain also decreased substantially. This report confirms long‐term efficacy of LVA for retroperitoneal lymphangiectasia as an alternative to sclerotherapy and surgical excision in the setting of previously failed treatments.